2020
DOI: 10.1177/0361198120918584
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rail Pad Stiffness on Vehicle–Track Dynamic Interaction Excited by Rail Corrugation in Metro

Abstract: Rail corrugation can cause intense dynamic interaction between train and track, which can reduce riding comfort and lifespan of track structure, and even threaten running safety. Instead of investigating the root cause and growth of corrugation, this case study aims to investigate possible solutions to the excess train–track dynamic interaction excited by rail corrugation in a metro track through both numerical analysis and field experiments. Numerical analysis was performed based on a vehicle–track coupled dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
1
6
0
2
Order By: Relevance
“…Bu durumda teker/ray etkileşiminden doğan titreşimler ray pedi ile sönümlenmeye çalışıldığı için ray pedi sistemin oldukça önemli bir parçasıdır. Ray pedi esneme direncindeki değişimler balastsız hattın mekanik tepkileri üzerinde önemli bir rol oynar [8]. Şekil 2(a)'da ray pedinin, W21 ray bağlantı sistemi içerinde kullanımı ve Şekil 2(b)'de kauçuk bir ray pedi örneği gösterilmiştir.…”
Section: Ray Pedleri Ve Hat üZerindeki Etkileriunclassified
See 1 more Smart Citation
“…Bu durumda teker/ray etkileşiminden doğan titreşimler ray pedi ile sönümlenmeye çalışıldığı için ray pedi sistemin oldukça önemli bir parçasıdır. Ray pedi esneme direncindeki değişimler balastsız hattın mekanik tepkileri üzerinde önemli bir rol oynar [8]. Şekil 2(a)'da ray pedinin, W21 ray bağlantı sistemi içerinde kullanımı ve Şekil 2(b)'de kauçuk bir ray pedi örneği gösterilmiştir.…”
Section: Ray Pedleri Ve Hat üZerindeki Etkileriunclassified
“…Teker/ray temas kuvvetleri: Yumuşak ray pedleri teker/ray temasının tahrip edici etkisini azaltır. Song ve diğerleri (2020), yaptıkları nümerik analizde ray pedinin teker/ray temas kuvvetlerini etkileyen en önemli parametre olduğu sonucuna ulaştılar [8]. Hiensch ve diğerleri (2002), Hollanda'da yaptıkları saha deneylerinde sert ray pedlerini yumuşak ray pedleriyle değiştirerek teker/ray etkileşiminin azaldığını gözlemlediler [18].…”
Section: Ray Pedi Esneme Direncinin Hat üZerindeki Etkileriunclassified
“…Therefore, it is more convincing to study the microscopic wheel-rail contact behaviors to reveal the formation mechanism of rail corrugation. For metro lines, rail corrugation mostly occurs in the small radius curve sections, and the corrugation of the inner rail is more serious than that of outer rail [29,30]. Meantime, abnormal rail corrugation with a short recurrence period also occurs in some large radius curves and straight sections [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [20] brought forward a cause theory of rail corrugation of friction induced torsional vibration, and explained that most of the corrugations occurred on the inner rail. By numerical analysis and field test, Song et al [21] discussed the solution to the excessive dynamic effect of vehicle-track system caused by rail corrugation. Ma et al [22] revealed the mechanism of corrugation according to the corrugation growth rate.…”
Section: Introductionmentioning
confidence: 99%